2019
DOI: 10.3949/ccjm.86a.18017
|View full text |Cite
|
Sign up to set email alerts
|

Breast augmentation surgery: Clinical considerations

Abstract: Women receive breast implants for both aesthetic and reconstructive reasons. This brief review discusses the evolution of and complications related to breast implants, as well as key considerations with regard to aesthetic and reconstructive surgery of the breast. KEY POINTSNearly 300,000 breast augmentation surgeries are performed annually, making this the second most common aesthetic procedure in US women (after liposuction).Today, silicone gel implants dominate the world market, and in the United States, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 41 publications
0
43
0
8
Order By: Relevance
“…Этот метод особенно эффективен для минимизации неудовлетворенности, поскольку он разделяет ответственность за процесс принятия решений. Также существуют компьютерные программы, помогающие подобрать имплантаты и наглядно показать пациенту ожидаемый результат [29].…”
Section: выбор формы и объема имплантатовunclassified
See 1 more Smart Citation
“…Этот метод особенно эффективен для минимизации неудовлетворенности, поскольку он разделяет ответственность за процесс принятия решений. Также существуют компьютерные программы, помогающие подобрать имплантаты и наглядно показать пациенту ожидаемый результат [29].…”
Section: выбор формы и объема имплантатовunclassified
“…Частота и характер осложнений после увеличивающей маммопластики достоверно не отличаются среди трансгендеров и среди женщин. Возможны такие осложнения, как капсульная контрактура, разрыв имплантата, развитие гематомы или кровотечения, инфекции или серомы раны, возникновение хронической боли, смещение имплантата, некроз соска, ареолы или лоскута, экструзия имплантата либо расслоение раны [29].…”
Section: возможные осложнения после аугментационной маммопластикиunclassified
“…Over 40% of the women who underwent a mastectomy were for breast reconstruction or disease-related plastic surgery; these women had been diagnosed with and surgically treated for regional breast cancer using modified radical mastectomy (MRM) (2). In their review article, Coombs et al (4) explored the literature on surgical procedures of breast augmentation and discussed the evolution of implants, patient assessments, and post-operative complications. Currently, aesthetic surgery offers innovative solutions that ensure the safety and well-being of women and are cognizant of their physical characteristics (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Surgeons must determine that candidates do not have body dysmorphic disorder or unrealistic expectations before operating. Several studies have reported that women who undergo breast augmentation surgery are more likely to use tobacco and alcohol, as well as higher anxiety levels, and are more likely to have a neurotic personality (7,8). It is vital that surgeons take these factors into consideration during preoperative patient assessment.…”
Section: Introductionmentioning
confidence: 99%